Analisis activity based costing dalam penentuan harga pokok produksi - Baviga, Rio; Amriana, Sela (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
In determining the cost of goods produced, the application of the Activity Based Costing method aims to prevent the company from making wrong decisions regarding the cost of goods produced. This study aims to determine the conventional cost accounting system applied by UD. Mebel Aldi and to find out the alternative application of the Activity Based Costing (ABC) system, in order to improve the accuracy of the calculation of the cost of goods manufactured (COGS). This research is a comparative descriptive method. The results of this study show that the cost of goods produced using the Activity Based costing method and the conventional system show that the calculation of the cost of goods produced causes distortion, namely Overcosting for the production of cabinets, tables, and chairs. The difference is burdened on factory Overhead costs that are not charged and detailed correctly by UD. Mebel Aldi.